A Scale for Measuring Entrepreneurial Orientation of Farmers’ Producer Companies towards Secondary Agriculture (Indian Journal of Extension Education, 2025)
The Farmers’ Producer Companies in India play an important role in secondary agriculture (an entrepreneurial endeavour) through collective action. The study was conducted in 2025 and aimed to construct a scale measuring the entrepreneurial orientation of FPCs’ member farmers in the context of secondary agriculture. Sixty statements were shortlisted after screening of 84 statements using Edwards’ criteria for relevancy test. Consequently, 38 items were observed as relevant by following the criteria RW > 0.80 and MRS > OMRS. The discriminatory power of scale was further tested using the t test with a cut-off value of 1.75. The final scale covered 38 items grouped under eight dimensions, namely innovativeness, proactiveness, risk-bearing ability, achievement motivation, self-confidence, management, market, and leadership orientation. The scale showed an excellent reliability, evidenced by Cronbach’s alpha value of 0.938. Split-half and Pearson correlation results obtained 0.824 and 0.907, respectively, which also confirmed high reliability. Validity was established through expert judgment. The scale may help policymakers and researchers design evidence-based interventions to strengthen agripreneurship and rural development.